Relative vulnerability of the different provinces of the Philippines to El Niño-induced droughts of various magnitudes - David, Wilfredo Pineda; de los Reyes, Mona Liza F.; Millare, Kirby Joselito L.; Fajardo, Arthur L. (2007)
Two base indices of drought magnitude were used to assess the relative vulnerability of the different provinces of the Philippines to El Niño-induced droughts. They are based on the cumulative departure of monthly rainfalls from their normal values during the period from the onset to the termination date of the effect of El Niño on Philippine rainfall. Area-weighted drought magnitudes associated with each of the eight El Niño events that occurred from 1971 to 2000 were estimated for the different areas or provinces, using the available monthly rainfall records from 73 rain gauging stations. For each province, the computed drought magnitudes for each index were subjected to frequency analysis. Drought magnitudes associated with various recurrence intervals were estimated. The drought magnitudes expected to be exceeded every two and five El Niño events were used to assess the relative vulnerability of the different provinces to El Niño-induced droughts. The results of the analysis showed that the provinces on the western seaboards of the bigger islands of Luzon, Panay and Mindanao were most vulnerable to El Niño-induced droughts. The provinces on the eastern seaboard of Mindanao and the eastern part of Cagayan Valley were least vulnerable. The provinces of Samar, Leyte, Masbate, Bicol, Central Luzon and Southern Luzon exhibited moderate to high vulnerability. Some smaller islands southwest of Luzon including Palawan, Mindoro and Romblon seemed to be less vulnerable to drought or had lower drought magnitudes associated with 50% probability of being exceeded. The base indices developed in this study provide a general measure for assessing the vulnerability of the different agro-ecological zones or provinces of the Philippines to El Niño-induced droughts. The component of the environment or the specific commodity or resource of interest would dictate which of the two indices would be more appropriate to use.
Keywords: El Niño; Vulnerability assessment